THE APPLICATION OF VISUAL MAPPING AS A NEW MEDIA TO SUPPORT THE ATMOSPHERE AND AMBIANCE IN MUSIC EVENTS - Tarumanegara, William (Universitas Ciputra, 2020)
So many music shows are held in Indonesia. Music shows are now also decorated by Video background or known as Visual Mapping. Visual Mapping is a new medium on the stage. This makes the writer want to make an observation on the atmosphere and ambiance provided by a Visual Mapping on a music event. Qualitative methods with observative techniques and interviews to obtain data and information needed to be used as a basis for data collection. The writer expects that visual mapping observation will be able to provide an explanation regarding visual mapping as a new media that provides an atmosphere & ambiance as well as a new experience for visitors. Keyword: Music Event, Motion Graphics, Video Mapping, Ambience, Media.